ADMINISTRATIVE TRANSGRESSION AND JUDICIAL DISCRETION FOR THE SAKE OF CITIZENS’ RIGHTS: The Legalisation of Unregistered Marriages in Indonesia - Fauzi, Muhammad Latif (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
This article addresses how the legalisation of unregistered marriages works in Indonesian day-to-day practices. It understands people’s strategies to legalise their unregistered marriage and examines the state activities of granting legalisation. It seeks to answer in what ways the legal validity of a marriage is important to Muslim citizens. The data in this paper results from the observation of marriage registration documents in a marriage registration office and the examination of legal reasoning used by Islamic judges in marriage legalisation (isbat nikah) cases. This essay emphasizes that state recognition of a marriage cannot entirely substitute community-based legal norms. It also shows the importance of administrative transgression and judicial discretion played by street-level bureaucrats. By so doing, they have grounds to accord legalisation. They apply a lenient approach towards marriage rules that is key to providing state recognition of unregistered marriages.[Abstrak: Tulisan ini membahas bagaimana legalisasi perkawinan tidak tercatat diterapkan dalam praktik sehari-hari di Indonesia. Tulisan ini memahami strategi masyarakat dalam melegalisasi ‘perkawinan tanpa pencatatan’ dan menganalisis alasan negara dalam memberikan legalisasi. Ini untuk menjawab pertanyaan sejauh mana status sah dalam perkawinan penting bagi warga negara Muslim? Data dalam tulisan ini dihasilkan dari pengamatan dokumen pencatatan nikah di kantor pencatatan nikah dan pemeriksaan atas penalaran hukum dalam kasus pengesahan perkawinan (isbat nikah). Tulisan ini menekankan bahwa pengakuan negara atas perkawinan tanpa pencatatan tidak dapat menggantikan norma yang berlaku di masyarakat. Praktik di lapangan menunjukkan pentingnya pelanggaran administratif dan diskresi yudisial yang dimainkan oleh para birokrat tingkat jalanan. Dengan cara demikian, mereka memiliki alasan untuk memberikan legalisasi. Mereka menerapkan pendekatan yang lunak terhadap aturan perkawinan yang merupakan kunci untuk dapat memberikan pengakuan negara atas perkawinan tanpa pencatatan.]